Mental Development Program to Increase Religious Values in Military Units : (Case study of Raider 300 Brawijaya Cianjur) - Edi Supardi; Asep Basuki Rahmat; Asep Kurniawan (Doctoral Program of Social Science Pasundan University, 2026)
The mental and spiritual development of Indonesian National Armed Forces (TNI) soldiers is a strategic aspect in developing professional military human resources with high moral integrity. The background of this research is based on the importance of ensuring that the Mental Development Program (BINTAL) is not merely administrative or ceremonial, but is truly internalized in the lives of soldiers. This study aims to analyze the implementation of the BINTAL Program, the level of soldiers' religiosity, and the supporting and inhibiting factors in strengthening the soldiers' personalities and ethics. The research method used is a descriptive qualitative approach with data collection techniques through observation, in-depth interviews, and documentation studies, which are analyzed using the mental development theories of Mangunhardjana and Zakiah Daradjat, as well as the religiosity theories of Glock and Stark. The results show that the implementation of the BINTAL Program has been structured and relevant to the soldiers' spiritual needs through routine religious studies, premarital briefings, and spiritual guidance that touches on practical and emotional dimensions. The level of soldiers' religiosity tends to be positive although varied, with ideological, ritualistic, experiential, intellectual, and consequential dimensions beginning to form. Supporting factors such as unit leadership, active spiritual guidance, and military discipline are pillars of success, while obstacles include the density of military activities and differences in religious backgrounds. This study confirms that the BINTAL Program is effective in developing religious, mentally resilient, and ethical soldiers when implemented with a humanistic, structured approach and supported by a strong organizational culture.